(untitled) (Bangladesh Journal of Medical Education, 2017)
This descriptive cross sectional study was carried out to assess the current status of practice of Quality Assurance Scheme(QAS) in different government and non-government medical colleges of Bangladesh. Principals/academic coordinators and students of all the medical colleges were the study population. Sample size were 13 principals/academic coordinators and 760 MBBS students of different phases. Convenience sampling technique was adopted to conduct the study. Two semi-structured self administered questionnaires one for the students and other for the principal/academic coordinator and one checklist were used to collect data from the respondents . Study revealed that 80.8% medical colleges have complete institutional framework of QAS and 68.1% medical colleges have fully functioning operational framework of QAS. Majority of the medical colleges (53.8%) do not have student representatives in academic coordination committee and only 23% medical colleges collected the phase wise evaluation of the course by the students. More than sixty one percent (61.54%) medical colleges have faculty development and review committee and 76.92% medical colleges have faculty development programme. Provision of exchange review visit by the academic coordinators is absent in 84.61% medical colleges. Almost all the medical colleges (92.31%) prepared and submitted the QAS report to NQAB in the last year. Regarding teaching learning 56.7% students were satisfied/very satisfied. A significant number of students (37.9%) gave negative opinion regarding recognition of students opinion in teaching learning. In the present study it was found that 9.1 % teachers of the selected medical colleges were engaged in research work in last year , 15.5% teachers had publication and 14.8% teachers presented scientific paper at various level in last year. Bangladesh Journal of Medical Education Vol.6(1) 2015: 2-7